Status And Prospects Of Aquaculture Practices In Barura Upazila, Comilla, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2013)
The present study was carried out in Barura upazila under Comilla district to assess the aquacultures status in 2008 and its future prospects. The upazila has no river but one Jolmohal (Carzon khal) occupying 700 ha, 7494 deghi and pukur (1836.77 ha), 6 khal (490 ha), 625 commercial and khas pukur (428.07 ha), 56 fish farms (92.57 ha) and paddy-cum fish culture (777.62 ha) which altogether formed vast fishery resources. In addition, 16 hatcheries with production capacity of 5350 kg and 56 nurseries with production capacity of 271.15 metric ton support necessary stocking fries and fingerlings for the above resources. In total 35% people are involved with aquaculture in the upazila. Thai Pangus (Pangasiadon hypopthalmus) and carp (rui, katla, mrigal etc.) are dominated cultured species in the study area. Semi-intensive culture systems are mostly used in this area. The upazila fulfills its own demand and the surplus fishes are sold to the neighboring districts. Only the Thai Koi ( Anabas testudineus) was found to be trading overseas. J. Asiat. Soc. Bangladesh, Sci. 39(1): 69-76, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16035